Lift and Drag Performance Based on Varying Flapping Wing Camber at Low Reynolds Number of Micro Air Vehicles (MAVs) - Yusoff, H.; Arifin, M.R.; Shaari, N.S.; Zainuddin, M.; Mahmod, R.; Suhaimi, S.; Wan Mohamed, W.M. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Flapping-Wing Micro Air Vehicles (FW-MAVs) are small hand-held flying vehicles that can maneuver in constrained space owing to their lightweight, low aspect ratio and the ability to fly in a low Reynolds number environment. In this study, the aerodynamic characteristics such as time-averaged lift (CL avg) and time-averaged drag (CD avg) of camber wings with different five wind tunnel test models with 6, 9, 12, and 15 per cent camber were developed and the results were compared with a flat wing to assess the effects of camber wing on the aerodynamic performance for flapping flight applications. The experiments were performed in an open chamber with non-return airflow with a test section of (0.3 x 0.3) m and capable of speeds from 0.5 to 30 m/s. The (CL avg) and (CD avg) as functions of the angle of attack at 100, associated with flapping frequency at 9 Hz and low Re = 3600 of the flapping motions concerning the incoming flows are measured by using a strain gauge balance and KYOWA PCD- 300A sensor interface data acquisition system. It is found that camber would bring significant aerodynamic benefits in a higher lift in comparison to the flat wing and increase with increasing camber instead of drag shows contrary a decreasing of performance with increase drag when the camber raised.